The Path of Ethnopsychologist: to the 70th Anniversary of Tatiana G. Stefanenko - Marina V Kotova; Natalia G Malysheva; Olga V Solovyova (Peoples' Friendship University of Russia (RUDN University), 2019)
This article is dedicated to the memory of Professor of the Faculty of Psychology of Lomonosov Moscow State University, a leading researcher in the ﬁeld of ethnopsychology in Russia - Tatyana Gavrilovna Stefanenko, who in 2019 would have turned 70 years old. The article deals with the main milestones of her life, pedagogical, scientiﬁc and practical work, touches upon the facets of her personality.